Implementasi Konsep Budaya 5R (Ringkas, Rapi, Resik, Rawat Dan Rajin) Sebagai Upaya Meningkatkan Kinerja Perusahaan Dari Sisi Non Keuangan - Iman Sidik Nusannas (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
5R or commonly known as 5R (Seiri, Seiton,Seiso, Seiketsu, Shitsuke) a Japanese work culture first applied in Japan is now spread to the world. This 5R motivate many enterprises to improve their work culture. This short study is to describe what is 5R, who should use this, and why it is powerful to increase a disciplin of an enterprise. Although has no direct relationship to increase profit, the kaizen way 5R will guide an enterprise to an eficient management on many sector of company.Key words: Kinerja Perusahaan, budaya perusahaan ,5R